If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3x + -10 = 0 Reorder the terms: -10 + 4x + -3x = 0 Combine like terms: 4x + -3x = 1x -10 + 1x = 0 Solving -10 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 1x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 1x = 0 + 10 1x = 0 + 10 Combine like terms: 0 + 10 = 10 1x = 10 Divide each side by '1'. x = 10 Simplifying x = 10
| (n-5)*10=27 | | 9-3(2x+5)+8x= | | 5lnx-3lny=0 | | y=0.1x^2-1.2x+7.6 | | 9-3(2x+5)+8x=equation | | 5-6k=5 | | (4/3)/x | | 3.14c=7927 | | 24+1=74 | | (8/2x)=(15/60) | | 3x+1+8x-9+5x-3=180 | | 27377=6786v | | 23=-4m+2-3m | | 1+4r=-15+6r | | 3x+-1=12x-64 | | 3(1/3)3 | | 5e+7e-9-e=84-4e | | (1/3)(1/3)(1/3)3=a | | 4/5y-8+=2/5+16 | | 8/2x=15/60 | | 7(k-3)= | | 2a+3b+7c= | | 3x+54y-12=0 | | 6(3-4y)= | | n+29=48 | | -4(-2b-7)=-44 | | 1.84/2.85=5.14/t | | 3i*x=y | | 2(5t-4)+6=40-t | | 49.2=1.5h | | 2(4m+1)=3 | | 114/95=95/x |